The Effects of Early-Life Predator Stress on Anxiety- and Depression-Like Behaviors of Adult Rats - Lu-jing Chen; Bing-qing Shen; Dan-dan Liu; Sheng-tian Li (Neural Plasticity)
Childhood emotional trauma contributes significantly to certain psychopathologies, such as post-traumatic stress disorder. In experimental animals, however, whether or not early-life stress results in behavioral abnormalities in adult animals still remains controversial. Here, we investigated both short-term and long-term changes of anxiety- and depression-like behaviors of Wistar rats after being exposed to chronic feral cat stress in juvenile ages. The 2-week predator stress decreased spontaneous activities immediately following stress but did not increase depression- or anxiety-like behaviors 4 weeks after the stimulation in adulthood. Instead, juvenile predator stress had some protective effects, though not very obvious, in adulthood. We also exposed genetic depression model rats, Wistar Kyoto (WKY) rats, to the same predator stress. In WKY rats, the same early-life predator stress did not enhance anxiety- or depression-like behaviors in both the short-term and long-term. However, the stressed WKY rats showed slightly reduced depression-like behaviors in adulthood. These results indicate that in both normal Wistar rats and WKY rats, early-life predator stress led to protective, rather than negative, effects in adulthood.